Poetry Translation as a Means to Intensify Sound Communication Between People of Different Cultures. (P.B.Shelley "Ode to the West Wind" From English into Albanian) - Poshi, Ilda (Mediterranean Journal of Social Sciences, 2012)
When the universe was created, the Word attached to its creation, since the word could serve as a tool that builds,coordinates, interprets, or destroys, confuses and disrupts any contact between people, events or a combination of the two. Everyindividual or event needs the word to bring about these processes or specifically to communicate. Communication is like a "galaxy" ofendless "constellation" chain-linked, which creates around it a muddled "vortex", which in turn reels up all the "stars" in a magneticbewitching breast. Thus, galaxies would be the world composed of people of different cultures (Pleiades) within which human knowledgedevelops (Vortex), which in turn reels up in its breast as if by magic all the communicative ways and norms between people (stars) . It isas beautiful process as it is complicated of individuals who share ideas, messaging etc. - whether expressed through voice or in writing.In fact, we recognize oral, written, visual, electronic, and last a form called non-verbal communication. However, all these forms ofcommunication invented by man or not have as proof, the Paper; everything is recorded in them for their existence. Writing as a form ofcommunication has several forms and one of them is Poetry. Poetry has been written since in the ancient times by writers who havecontributed in various countries, subsequently it has also been translated. In England, the period of Romanticism, records one of themost typical writers: Percy Bysshe Shelley. In this paper, we will treat the lyric poem "Ode to the West Wind" and the Albanian versionâ€œOdÃ« pÃ«r ErÃ«n e PerÃ«ndimitâ€ to highlight the value of poetry as a way to intensify sound communication between people of differentcultures.